Time course of symptoms during the development of a parasympathetic overtraining syndrome - Brechtel, L. M.; Braumann,K. M.; Wolff, R. (Medicine & Science in Sports & Exercise, 1999)
The effects of seven weeks of overtraining (increased training volume and intensity) on long-distance runners (N = 7) were evaluated weekly. Symptoms of overload (overreaching) emerged after three weeks of training, and overtraining was exhibited after 5.5 weeks of the experience. The total number of musculo-skeletal, health, sleep, and mood changes increased in overload training, but were reduced, but not back to normal, in overtraining. Disruptive symptoms remained for up to four weeks after termination of the study.